Modification of control system using PLC and HMI on drill oil hole machine to speed up piston model replacement process time in automotive manufacturing industry - Ardi, Syahril; Febriansyah, Mohamad Bintang; Hidayat, Muhammad; Fairus, Sirin; Suprapto, Heru (Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This research was conducted at an automotive manufacturing company that produces pistons. In the piston production process, there are two stages, the first stage is the casting process which can be called the Foundry process, and the second stage is the manufacture of parts which can be called the Machining process. In the Machining process, there is a piston drilling process to make oil holes using a Drill Oil Hole (DOH) machine. The Drill Oil Machine process has a clamping process using a pneumatic cylinder, then determining the points using a servo motor, and the drilling process using a selfeeder motor. This Drill Oil Hole machine has a weakness, namely it still uses the old control system, NC. This NC Control System program cannot be changed, and to change the program, you must contact the vendor directly. In addition, Troubleshooting takes a long time. Therefore, this study aims to change the control system from NC to PLC. This is done by adding a piston template system to reduce downtime and change the piston type model"”furthermore, changes to the HMI display on the DOH machine layer using the Omron NB10W HMI. Meanwhile, the servo motor and its driver use Servo Delta Asda-A2. After replacing the control system from NC-based to PLC CJ2M CPU-11, the DOH machine testing was carried out by the provisions. The use of HMI as the basis for monitoring and the machine operating system by the operator makes it much easier to operate and has several additional features such as piston templates and sensor indicators that are not available in numerical-based control systems. In addition, for the next piston model replacement process, there is no more machine downtime.